Sexual and gender-based violence in areas of armed conflict: a systematic review of mental health and psychosocial support interventions - Tol, Wietse A (BioMed Central, 2013)
BACKGROUND: Sexual and other forms of gender-based violence are common in conflict settings and are known risk factors for mental health and psychosocial wellbeing. We present findings from a systematic review of the academic and grey literature focused on the effectiveness of mental health and psychosocial support interventions for populations exposed to sexual and other forms of gender-based violence in the context of armed conflicts. METHODS: We searched the Cochrane Database of Systematic Reviews, Cochrane Controlled Trials Register, PubMed/ Medline, psycINFO, and PILOTS, as well as grey literature to search for evaluations of interventions, without date limitations. RESULTS: Out of 5,684 returned records 189 full text papers were assessed for eligibility. Seven studies met inclusion criteria: 1 non-randomized controlled study; 3 non-controlled pre- post-test designs; 1 retrospective cohort with a matched comparison group; and 2 case studies. Studies were conducted in West and Central Africa; Albania; UK and USA, included female participants, and focused on individual and group counseling; combined psychological, medical, social and economic interventions; and cognitive behavioral therapy (two single case studies). CONCLUSIONS: The seven studies, while very limited, tentatively suggest beneficial effects of mental health and psychosocial interventions for this population, and show feasibility of evaluation and implementation of such interventions in real-life settings through partnerships with humanitarian organizations. Robust conclusions on the effectiveness of particular approaches are not possible on the basis of current evidence. More rigorous research is urgently needed.